Complex basis of hybrid female sterility and Haldane's rule in Heliconius butterflies: Z‐linkage and epistasis. Issue 3 (26th November 2021) - Rosser, Neil; Edelman, Nathaniel B.; Queste, Lucie M.; Nelson, Michaela; Seixas, Fernando; Dasmahapatra, Kanchon K.; Mallet, James
Abstract: Hybrids between species are often sterile or inviable. Hybrid unfitness usually evolves first in the heterogametic sex—a pattern known as Haldane's rule. The genetics of Haldane's rule have been extensively studied in species where the male is the heterogametic (XX/XY) sex, but its basis in taxa where the female is heterogametic (ZW/ZZ), such as Lepidoptera and birds, is largely unknown. Here, we analyse a new case of female hybrid sterility between geographic subspecies of Heliconius pardalinus . The two subspecies mate freely in captivity, but female F1 hybrids in both directions of cross are sterile. Sterility is due to arrested development of oocytes after they become differentiated from nurse cells, but before yolk deposition. We backcrossed fertile male F1 hybrids to parental females and mapped quantitative trait loci (QTLs) for female sterility. We also identified genes differentially expressed in the ovary as a function of oocyte development. The Z chromosome has a major effect, similar to the 'large X effect' in Drosophila, with strong epistatic interactions between loci at either end of the Z chromosome, and between the Z chromosome and autosomal loci on chromosomes 8 and 20. By intersecting the list of genes within these QTLs with those differentially expressed in sterile and fertile hybrids, we identified three candidate genes with relevant phenotypes. This study is the first to characterize hybrid sterility using genome mapping in the Lepidoptera and shows that it is produced by multiple complex epistatic interactions often involving the sex chromosome, as predicted by the dominance theory of Haldane's rule.